Protection of children's online privacy in Malaysia - Ayub, Zainal Amin (2017)
Purpose - The advantage of digital era with borderless world and having unlimited access to the Internet, enjoyed by most, if not all people, including the young or children. While the current millennials (Lenhart, Purcell, Smith, & Zickuhr, 2010) are more computer savvy than their parents (Heckman, 1999), children are also well versed with Internet and enjoy the digital access at the very young age.However, policy-makers are concern with the advancement of Internet and propagates the idea of shielding and segregating the children from the harm that may cause from access to the Internet (Allen, 2001). Also, Kumaran (2016) highlighted that although there are many benefit and advantages of the Internet but the harm and dangers it poses to the children is worrying because the informational privacy of the children is threatened by children’s participation in the digital world. Moreover, children are unconcern with their privacy, or do not know how to protect their informational privacy and data protection which are of concern to adults (Allen, 2001) and they are unaware the consequence and the impact of revealing their personal information, either their own data or their family data. Some countries have enacted specific legislations to protect the privacy of the children like the Children’s Online Privacy Protection Act (COPPA) in the United States of America (Hetcher, 2000) or introduced self-regulatory initiatives on online child privacy like in the European Union (EU) (Macenaite, 2016). At the international level, the Convention on the Rights of the Child (CRC) was introduced in 1989 by the United Nation (Lundy, 2012) to generally protect the children. The CRC acknowledges that the children is a group of people that needs extra care and protection. In Malaysia, the government has introduced the Child Act 2001 and the Sexual Offences Against Children Act 2017 that protect the children. However, how far these two Acts protect the online privacy of the children in Malaysia? As such, the paper seeks to examine the legal protection of online children privacy in Malaysia, focusing on the Child Act 2001.